Evaluating the effectiveness of undergraduate clinical education programs. Issue 1 (1st January 2020) - Ragsdale, John W.; Berry, Andrea; Gibson, Jennifer W.; Herber-Valdez, Christiane R.; Germain, Lauren J.; Engle, Deborah L.
ABSTRACT: Medical schools should use a variety of measures to evaluate the effectiveness of their clinical curricula. Both outcome measures and process measures should be included, and these can be organized according to the four-level training evaluation model developed by Donald Kirkpatrick. Managing evaluation data requires the institution to employ deliberate strategies to monitor signals in real-time and aggregate data so that informed decisions can be made. Future steps in program evaluation includes increased emphasis on patient outcomes and multi-source feedback, as well as better integration of existing data sources.